Peran Kelompok Kerja Inklusi dalam Meningkatkan Kualitas Hidup Kelompok Rentan di Desa Simbang, Kabupaten Maros - Sakinah Sakinah; Saifuddin Saifuddin; Mario Mario (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
This research analyzes the role of the Inclusion Working Group (IWG) in improving the quality of life of vulnerable groups in Simbang Village, Maros Regency, using a descriptive qualitative approach. Vulnerable groups such as people with disabilities (35 people: 14 men, 21 women) faced barriers to accessing public services, social stigma, and economic limitations before the KKI was established in 2022 through the INKLUSI-BaKTI Program. KKI serves as a bridge between the community and village government to realize inclusive development in accordance with Village Law No. 6/2014, filling a gap in the study of local institutions at the village level. The research methods involved in-depth interviews, participatory observation and documentation with purposive informants from KKI members, village officials and vulnerable groups. Data were analyzed through reduction, display, and verification with source triangulation to ensure validity. The results show that KKI plays a role in valid data collection, assistance in accessing services (Disdukcapil, social assistance), policy advocacy (Musrenbang), and economic empowerment through MSME training, which increases social participation, self-confidence, and the quality of life of vulnerable groups. Although structural challenges such as workspace and budget and social challenges such as family stigma still exist, KKI has succeeded in transforming the status of vulnerable groups from objects of pity to active subjects, in line with the SDGs “No One Left Behind”. This research contributes to the sociological study of social inclusion and provides practical input for responsive village policies. Key suggestions include strengthening KKI facilities and anti-stigma socialization for sustainability of inclusion.